Knowledge and practice of standard precautions towards prevention of needle stick injury among nursing students / Nur Adilah Mohd Rodzali @ Md Ghazali, Nur Amalina Idzani and Zalwani Hamid - Mohd Rodzali @ Md Ghazali, Nur Adilah; Idzani, Nur Amalina; Hamid, Zalwani (Faculty of Health Sciences, 2015)
Background: Needle stick injury is a major work-related hazards that highly exposing the health care workers to harmful blood-borne pathogens. Implementation of standard precaution is important to reduce the risk of needle stick injury. Nursing students’ knowledge together with high application of the practice would promote changes for better outcome to every hospital personnel including nursing students. The safety measures in handling sharp instruments would reduce the incidence of blood-borne disease infection among nursing students especially. Objective: This study aimed to determine knowledge and practice on standard precautions and blood borne disease among Universiti Teknologi MARA (UiTM) and University of Malaya (UM) nursing students. Method: Cross-sectional study conducted at UiTM and UM. The data were collected using the original version of the close-ended questionnaire from (Rampal, Zakaria, Leong, & Md Zain, 2010). A total of 116 nursing students participated in this study. Results: There was no significant difference regarding knowledge of standard precautions and blood-borne disease between nursing students from UiTM and UM with p=0.623 and p=1.732 respectively. The finding on the comparison on practice of standard precaution showed that there is no significant difference except on the questions involving practice of wearing gloves during withdrawing needle from patient (p= 0.012). Conclusion: The overall scores for nursing students in knowledge of standard precaution and blood borne disease showed good knowledge information and on compliance of practice on standard precaution. However, there is very little significant difference on knowledge of standard precaution and blood-borne disease between UiTM and UM. Besides, there is also very little significant difference on practice of standard precaution between both universities. Present findings suggest there is improvement in knowledge and practice of standard precaution among nursing students.